The microeconometric estimation of treatment effects: an overview - Marco Caliendo; Reinhard Hujer (Institute for the Study of Labor (IZA), 2005)
The need to evaluate the performance of active labour market policies is not questioned any longer. Even though OECD countries spend significant shares of national resources on these measures, unemployment rates remain high or even increase. We focus on microeconometric evaluation which has to solve the fundamental evaluation problem and overcome the possible occurrence of selection bias. When using non-experimental data, different evaluation approaches can be thought of. The aim of this paper is to review the most relevant estimators, discuss their identifying assumptions and their (dis-)advantages. Thereby we will present estimators based on some form of exogeneity (selection on observables) as well as estimators where selection might also occur on unobservable characteristics. Since the possible occurrence of effect heterogeneity has become a major topic in evaluation research in recent years, we will also assess the ability of each estimator to deal with it. Additionally, we will also discuss some recent extensions of the static evaluation framework to allow for dynamic treatment evaluation.
Keywords: C40; H43; J68; 330; evaluation; effect heterogeneity; matching; dynamic treatments; Arbeitsmarktpolitik; Wirkungsanalyse; Mikroökonometrie; Theorie